Cerebellar Volume Ratio to Total Intracranial in Central Causes of Vertigo: A Stereological Study - Gocmen-Mas, N.; Karabekir, S.; Yilmaz, O. Kusbeci; Sahin, B.; Ertekin, T.; Bas, O.; Senan, S. (Nature Publishing Group, 2009)
…
24th International Symposium on Cerebral Blood Flow and Metabolism/9th International Conference on Quantification of Brain Function with PET -- JUN 29-JUL 03, 2009 -- Chicago, IL